KANDUNGAN LOGAM TOTAL Pb DAN Cu PADA SAYURAN DARI SENTRA HORTIKULTURA DAERAH BEDUGUL - Henny Kurnia Ratnasari, G. A.; Siaka, I M.; Dwi Adhi Suastuti, Ni G. A. M. (Jurnal Kimia (Journal of Chemistry), 2013)
This paper discusses the determination of total metal content of Pb and Cu in vegetables from horticultural center of Bedugul area. Determination of the metals was performed by applying digestion method to the samples. Reverse aqua regia (a mixture of HNO 3 and HCl, 3:1) was used to digest the samples in an ultrasonic bath for 45 min at 60° C, followed by heating on a hotplate for 45 minutes at 140 o C. Solution resulted from the digestion was analyzed by the use of atomic absorption spectrophotometer (AAS) to determine metal concentrations of Pb and Cu through standard calibration curve. The results showed that Pb and Cu metals accumulated in 6 types of vegetables were varied. It was found that carrots contained the highest Pb (13.7218 mg/kg), while the lowest concentration of Pb was found in cabbage (1.4912 mg/kg). Meanwhile, the highest Cu metal content was found in celery which was 2.8073 mg/kg, but the lowest in sprouts i.e 0.7830 mg/kg.
Keywords: Vegetable, Metals, Pb, Cu